HUBUNGAN LAMA TINGGAL DENGAN TINGKAT KECEMASAN PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA PUSPAKARMA MATARAM - Putu Veny Surya Pratiwi; Danang Nur Adiwibawa; Dina Qurratu Ainin; Irwan Syuhada (Nusantara Hasana Journal, 2022)
Increased life expectancy is directly proportional to the increasing number of elderly in the world and West Nusa Tenggara. The elderly will experience the changes directed at the deterioration of physical’s and psychological’s health. Mental health problems that commonly occur in the elderly are depression, anxiety, loneliness and feelings of sadness. Some elderly do not get care from the family due to several factors, such as not having a family, therefore the social’s institution is a place for the elderly to get an good and appropriate care. In the process of environmental adaptation will be assessed through the length of stay of the elderly at the social institution and depend on the elderly physical condition which decreases because of aging process that demand setbacks in process of the new environmental adaptation. The condition will be worried by the elderly. Excessive worried is one of the psychological symptom that shows the existence of anxiety in the elderly. Purpose to identification the relationship between length of stay with anxiety level on elderly in the Social’s Intitution of Tresna Werdha Puspakarma Mataram. This study used an observational analytic, with cross sectional design. Data analysis using rank spearman. The significance results obtained from rank spearman test for the relationship between length of stay with anxiety’s level has value 0,000 (p<0.05). the coefficient value is -0.784, with the relationship is strong and the direction is negative, which short length of stay make higher risk incidence on anxiety. There is a significance results relationship between length of stay with anxiety level on elderly in the Social’s Intitution of Tresna Werdha Puspakarma Mataram.